Prosedur Operasional Analisis SWOT dalam Menetapkan Arah Kebijakan Prioritas Perusahaan - Rahayu Mardikaningsih; Alvina Rohma Irsyadiyyah; Andini Ika Arianti; Didit Darmawan (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2026)
This conceptual study examines how SWOT analysis can determine corporate strategic priorities through systematic connections between strengths, weaknesses, opportunities, and threats. A qualitative literature review method was employed, designed to collect, identify, and analyze relevant scholarly sources systematically. Findings indicate that priority determination requires four sequential steps: factor identification with verification and weighting, connection of internal to external factors, selection of highest synergy pairs, and translation into action plans. Strength opportunity pairs produce aggressive priorities. Weakness opportunity pairs produce remedial priorities. Strength threat pairs produce defensive priorities. Weakness threat pairs produce survival priorities. Weighting and urgency assessment prevent equal treatment of unequal factors. Periodic reanalysis maintains relevance amid environmental change. SWOT serves as exploration tool rather than justification tool when organizational culture supports intellectual honesty. Theoretical implications include enriching strategic management literature with operational procedures. Practical implications require managers to allocate sufficient time for cross factor connection processes